2018
DOI: 10.1111/bju.14237
|View full text |Cite
|
Sign up to set email alerts
|

Guideline of guidelines: primary monotherapies for localised or locally advanced prostate cancer

Abstract: Decisions regarding the primary treatment of prostate cancer depend on several patient- and disease-specific factors. Several international guidelines regarding the primary treatment of prostate cancer exist; however, they have not been formally compared. As guidelines often contradict each other, we aimed to systematically compare recommendations regarding the different primary treatment modalities of prostate cancer between guidelines. We searched Medline, the National Guidelines Clearinghouse, the library o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…However, overdiagnosis and overtreatment were frequently discussed in the last decade. Active surveillance (AS) is offered for suitable patients who have a very low or low‐risk disease to prevent overtreatment in the management of PCa …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overdiagnosis and overtreatment were frequently discussed in the last decade. Active surveillance (AS) is offered for suitable patients who have a very low or low‐risk disease to prevent overtreatment in the management of PCa …”
Section: Introductionmentioning
confidence: 99%
“…Active surveillance (AS) is offered for suitable patients who have a very low or low-risk disease to prevent overtreatment in the management of PCa. 3 Despite the improvements such as multiparametric prostate MRI (mp-MRI), and molecular technologies in PCa diagnostic tools, AS is also a controversial topic. 4 This controversy might be based on several factors including the tumor heterogenity, multifocality, and the biopsy undersampling which are associated with Gleason upgrading (GU) after RP.…”
Section: Introductionmentioning
confidence: 99%
“…Another study on PCa followed-up for 20 years also showed that RP does not significantly reduce all-cause mortality or tumor-specific mortality compared with AS, and RP results in associated complications11. Nearly 30% of patients require other treatments, such as surgery and radiotherapy, within 5 years of AS12, but AS is still widely used and recommended for patients with LRPC 1, 8. The 2014 edition of the CUA guidelines proposed an indication of AS for PCa confirmed by prostate biopsy, which was similar to other indications 4-6.…”
Section: Discussionmentioning
confidence: 99%
“…All guidelines except the Chinese Urological Association(CUA), including the American Urological Association, the European Association of Urology (EAU), the Japanese Urological Association, and the Canadian Urological Association currently have clear recommendations for treating low-risk prostate cancer (LRPC). Among them, active monitoring or surveillance (AS) is the most widely advised treatment 1. If LRPC is treated with radical prostatectomy (RP) or radiotherapy, it may be overtreated, which has no benefit to the patient and increases the complication rate2, 3 and wastes limited medical resources, leading to delayed treatment opportunities for those who have more aggressive prostate cancer (PCa).…”
Section: Introductionmentioning
confidence: 99%
“…Radical prostatectomy (RP), low-dose-rate brachytherapy (LDR), and external beam radiation therapy (EBRT) are the three major de nitive treatment options for localized prostate cancer. Established clinical guidelines recommend that treatment decisions should be made based on tumor features, baseline prostate speci c antigen (PSA) levels, patient age, comorbidity, life expectancy, and quality of life (3)(4)(5). However, which of these treatments is the best for patients with localized prostate cancer remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%